Enhancing The Quality of Life Using Multiliteracies Project Approach to Augment Employability Skills Among Malaysian University Graduates - Puteh-Behak, F.; Selamat, S.; Mohd Muzhafar Idrus; Darmi, R.; Mat Saad, N.S.; Massari, N.; Hazlina Abdullah (Universiti Sains Islam Malaysia, 2024)
The high unemployment rate among Malaysian university graduates is often associated to the lack of English communication and technological skills among the graduates. This study explores the utilization of Multiliteracies Project Approach in augmenting employability skills among the graduates. This qualitative study was conducted at a public university in Malaysia, involving 50 students in an English communication course. Data was collected through observation, interviews and reflective journals and data was analyzed using a thematic analysis. Findings show that the use of MPA developed the students' English language communication skills and technological knowledge. The findings also provide a significant pedagogical implication.